CULTURE AND HISTORY THROUGH WINE IN ITALY AND GREECE - Manola Maria; Angelopoulos Marios (E-Journal of Cultural Studies, 2021)
The purpose of this paper is to present the phenomenon of wine-making in Greece and Italy. To highlight the characteristics of wine tourism in those countries either positive or negative. Also the “Road of wine” in both countries is analyzed and the way they manage this event to welcome tourists and locals who want to learn more things about local wine. The first section analyzes the definition of tourism, tourist incentive, forms of alternative tourism and the consequences arising from tourism on the economy and society. The second section analyzes the history of wine in Greece and Italy. Immediately after, the classification of the wine is developed based on the aging time but also based on the color. The concept of wine tourism and its goals are also being developed. The third section mentions the routes of the Peloponnese in general and in particular which wineries and which places / islands take part in the event. Immediately after, the routes of wineries of Achaia are analyzed in the event “Wine Road”. Then it is mentioned how the event “Wine Road” started in Italy and especially in Venice. Keywords: Cultural heritage, Wine history, Italy, Greece, Culture, Wine roads .